2014
DOI: 10.4267/2042/53977
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific role of calcium sensing receptor

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…NF‐ κ B is considered as a cardinal transcriptional regulator of inflammatory gene expression and it has been recently established that different forms of NF‐ κ B could have different functions in the inflammatory responses . It is also well documented that NF‐ κ B plays a crucial role in the synthesis of cytokines such as TNF‐ α , IL‐1 β , IL‐6 and IL‐8 and also regulates the expression of COX‐2 .…”
Section: Pathways Of Chronic Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…NF‐ κ B is considered as a cardinal transcriptional regulator of inflammatory gene expression and it has been recently established that different forms of NF‐ κ B could have different functions in the inflammatory responses . It is also well documented that NF‐ κ B plays a crucial role in the synthesis of cytokines such as TNF‐ α , IL‐1 β , IL‐6 and IL‐8 and also regulates the expression of COX‐2 .…”
Section: Pathways Of Chronic Inflammatory Responsementioning
confidence: 99%
“…This review aims to discuss various molecular targets and underlying mechanisms of food protein-derived anti-inflammatory peptides and to explore their potential against various chronic inflammatory diseases.The two main pathways for chronic inflammation are the NF-B pathway and the MAPK-JNK pathway.NF-B is considered as a cardinal transcriptional regulator of inflammatory gene expression and it has been recently established that different forms of NF-B could have different functions in the inflammatory responses. 4,49 It is also well documented that NF-B plays a crucial role in the synthesis of cytokines such as J Sci Food Agric 2016; 96: 2303-2311…”
mentioning
confidence: 99%
“…The Beclin1 protein is a core element of autophagy; the post‐translational modifications of the Beclin1 interactome components include the Beclin1 protein, Bcl‐2 family, Type 3 phosphatidyl inositol 3 kinase (T3PI3K), and autophagy‐related 14 homolog (ATG14L), which is activated to produce phosphatidyl inositol‐3 kinase (PI3K). These factors are known to play important roles in the regulation of cellular autophagy, and it was recently shown that Beclin1‐mediated autophagy is involved in several neurological diseases . However, its precise role in diabetes‐induced cognitive dysfunction remains unclear.…”
Section: Introductionmentioning
confidence: 99%